2012
DOI: 10.1099/vir.0.043232-0
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear translocation of adeno-associated virus type 2 capsid proteins for virion assembly

Abstract: 3Roslin Cellab, Roslin BioCentre, Roslin, Midlothian EH25 9PP, UK Adeno-associated virus (AAV) capsid assembly occurs in the nucleus. Newly synthesized capsid proteins VP1, VP2 and VP3 contain several basic regions (BRs), which may act as nuclear localization signals (NLSs). Mutation of BR2 and BR3, located at the VP1 and VP2 N termini, marginally reduced nuclear uptake of VP1 or VP2, but not of VP3, when expressed in the context of the whole AAV type 2 (AAV2) genome. Combined mutation of BR1, BR2 and BR3 resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
(83 reference statements)
0
19
0
Order By: Relevance
“…The N termini of both VP1 and VP2 incorporate the so-called basic region 3 (BR3; PKRKKART) representing conservative nuclear localization sequence (NLS) motif, which is necessary for AAV to deliver its genome within the nucleus and subsequently transduce the cells. [27][28][29] It is thus not surprising that a 3-fold increase of each VP1 and VP2 increases the yield of a more infectious virus.…”
Section: Discussionmentioning
confidence: 99%
“…The N termini of both VP1 and VP2 incorporate the so-called basic region 3 (BR3; PKRKKART) representing conservative nuclear localization sequence (NLS) motif, which is necessary for AAV to deliver its genome within the nucleus and subsequently transduce the cells. [27][28][29] It is thus not surprising that a 3-fold increase of each VP1 and VP2 increases the yield of a more infectious virus.…”
Section: Discussionmentioning
confidence: 99%
“…It has to be determined whether these mutant VPs are also defective in AAP binding. A very interesting VP mutation in this respect is K688A/K692A in the protein's C terminus, which produces a strong assembly defect (18). Although AAP is able to bind to the mutated VP (data not shown) and accumulates in the nucleus, it does not accumulate in the nucleoli and is deposited in nuclear speckles.…”
Section: Discussionmentioning
confidence: 99%
“…Although coprecipitation of VP with antibodies against the AAP-fused AU1 tag was reproducible, the recovery of AAP in the immunoprecipitate was (3,26) are shown in blue. Mutant constructs described in this study and by Popa-Wagner et al (18) are shown in red, while the B1 antibody epitope is shown in green. Note the clustering of assembly mutant constructs at the 2-fold symmetry axes.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Fig. 3h, it is an adeno-associated viral capsid consisting of VP1 (full-length VP protein), VP2 (lacking uVP1), and VP3 (lacking nuclear localization signal, NLS), but not VP4, with a ratio of around 1:1:10 [148,149]. Why do all VPs contain the same receptor-binding site?…”
Section: Parvoviridaementioning
confidence: 99%